Join the IDNLearn.com community and get your questions answered by experts. Get accurate and comprehensive answers from our network of experienced professionals.
Sagot :
Sure, let's carefully understand the relevant concepts and arrive at the correct answer.
1. Original Conditional Statement:
The given conditional statement is [tex]\( p \rightarrow q \)[/tex]. This means "if [tex]\( p \)[/tex], then [tex]\( q \)[/tex]".
2. Understanding Contrapositive:
The contrapositive of a conditional statement [tex]\( p \rightarrow q \)[/tex] is formed by negating both the hypothesis and the conclusion, and then reversing them. So, the contrapositive of [tex]\( p \rightarrow q \)[/tex] is [tex]\( \sim q \rightarrow \sim p \)[/tex].
3. Explanation of Choices:
- [tex]\( q \rightarrow p \)[/tex]: This is the converse of the conditional statement, not the contrapositive.
- [tex]\( \sim q \rightarrow \sim p \)[/tex]: This is the negation and reversal of both parts of the original statement, which is the correct formation of the contrapositive.
- [tex]\( p \rightarrow q \)[/tex]: This is the original statement itself, not the contrapositive.
- [tex]\( \sim p \rightarrow \sim q \)[/tex]: This is the inverse of the conditional statement, not the contrapositive.
4. Conclusion:
Based on the conceptual understanding above, the contrapositive of the original conditional statement [tex]\( p \rightarrow q \)[/tex] is [tex]\( \sim q \rightarrow \sim p \)[/tex].
Thus, the correct answer is:
[tex]\[ \sim q \rightarrow \sim p \][/tex]
Therefore, the correct representation of the contrapositive of the conditional statement [tex]\( p \rightarrow q \)[/tex] is [tex]\( \sim q \rightarrow \sim p \)[/tex].
1. Original Conditional Statement:
The given conditional statement is [tex]\( p \rightarrow q \)[/tex]. This means "if [tex]\( p \)[/tex], then [tex]\( q \)[/tex]".
2. Understanding Contrapositive:
The contrapositive of a conditional statement [tex]\( p \rightarrow q \)[/tex] is formed by negating both the hypothesis and the conclusion, and then reversing them. So, the contrapositive of [tex]\( p \rightarrow q \)[/tex] is [tex]\( \sim q \rightarrow \sim p \)[/tex].
3. Explanation of Choices:
- [tex]\( q \rightarrow p \)[/tex]: This is the converse of the conditional statement, not the contrapositive.
- [tex]\( \sim q \rightarrow \sim p \)[/tex]: This is the negation and reversal of both parts of the original statement, which is the correct formation of the contrapositive.
- [tex]\( p \rightarrow q \)[/tex]: This is the original statement itself, not the contrapositive.
- [tex]\( \sim p \rightarrow \sim q \)[/tex]: This is the inverse of the conditional statement, not the contrapositive.
4. Conclusion:
Based on the conceptual understanding above, the contrapositive of the original conditional statement [tex]\( p \rightarrow q \)[/tex] is [tex]\( \sim q \rightarrow \sim p \)[/tex].
Thus, the correct answer is:
[tex]\[ \sim q \rightarrow \sim p \][/tex]
Therefore, the correct representation of the contrapositive of the conditional statement [tex]\( p \rightarrow q \)[/tex] is [tex]\( \sim q \rightarrow \sim p \)[/tex].
Your presence in our community is highly appreciated. Keep sharing your insights and solutions. Together, we can build a rich and valuable knowledge resource for everyone. For trustworthy and accurate answers, visit IDNLearn.com. Thanks for stopping by, and see you next time for more solutions.